On the Determinants of Labour Market Institutions: Rent-Sharing vs. Social Insurance - Jonas Agell (Center for Economic Studies and ifo Institute (CESifo), 2000)
What determines the structure of labour market institutions? This paper argues that common explanations based on rent sharing are incomplete; unions, job protection, and egalitarian pay structures may have as much to do with social insurance of otherwise uninsurable risks as with rent sharing and vested interests. In support of this more benign complementary hypothesis the paper presents a range of historical, theoretical, and cross-country regression evidence. The social insurance perspective changes substantially the assessment of often-proposed reforms of European labour market institutions. The benefits from eliminating labour market rigidities have to be set against the costs of reduced coverage of human capital related risk. The paper also argues that it is unclear whether the forces of globalisation, and the new economy, will really force countries to make their labour markets more flexible. While these phenomena may increase the efficiency costs of existing institutions, they may also make people more willing to pay a high premium to preserve institutions that provide insurance.
Keywords: 330; Labour market institutions; comparative historical evidence; Sweden; Massachusetts; rent seeking; social insurance; union models; cross-country regressions; openness; linguistic fractionalisation